THE NOTION OF CONCEPTUAL INTEGRATION THEORY (Texas Journal of Multidisciplinary Studies, 2022)
The article is devoted to the problem of conceptual blending representation. As cognitive linguistics is of special interest to the researchers from the end of the XXth century till the present time, theory of conceptual blending has become one of the most important directions in modern linguistics. Conceptual blending is understood as a mental process of creating a new meaning by joining already existed concepts which have their own particular meanings. The process is based on four mental spaces such as generic space, input space 1, input space 2 and blended space which are considered to be small conceptual interconnected elements